Cross-sectional imaging of the Fontan circuit in adult congenital heart disease. Issue 6 (June 2015) - Lewis, G.; Thorne, S.; Clift, P.; Holloway, B.
Abstract : The Fontan circuit is the result of a palliative surgical procedure that is performed in patients with a functionally single ventricle cardiac anomaly. The success of this operation has resulted in an increasing population of adults with this anatomy and physiology. The purpose of this article is to familiarize the general radiologist with the expected anatomy and cross-sectional imaging findings, highlight special imaging considerations, and examine the common complications that are encountered in this group of patients.